Influencia de la estrategia didáctica “Medios – Fin” en el aprendizaje de la resolución de problemas matemáticos de los alumnos del 4to grado de primaria de la I.E.E. José Carlos Mariátegui - Izquierdo Romero, Rosario (2011)
The investigation has had for aim develop the didactic strategy "Means - end "in the learning resolution of mathematical problems in the pupils of the fourth degree of primary education in the district of Rioja. The hypothesis, it was formulated in the supposition that the didactic strategy "Means - end" influences significantly in the learning resolution of mathematical problems. The variables are organized in two: independent variable represented by the didactic strategy "Means - end" and dependent variable, which refers to the learning resolution of mathematical problems. The study developed with 9 students that it corresponds to the sample of study, determined by means of the sampling not probabilístico accidental. The investigation is of type applied, of experimental level, of design of preprueba - posprueba with an alone group, which is located in preexperimental designs. To the students a test applied type questionnaire befare and after the application of the didactic strategy means - end. The processing of information threw that the application of the didactic strategy "Means- end", has influenced significantly the learning of the resolution of mathematical problems the pupils of the fourth degree of primary education of the Educational Experimental lnstitution "Jase Carlos Mariátegui" of the district of Rioja the year 201 O.